1999
DOI: 10.1046/j.1439-0418.1999.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flowers on the demography of western flower thrips Frankliniella occidentalis (Thysan., Thripidae)

Abstract: The impact of~owers on the population growth of Frankliniella occidentalis was characterized on wax~ower plants\ Impatiens walleriana[ In the presence of~owers\ the populations grew exponentially while in their absence\ the thrips populations only maintained themselves and showed no growth The di}erence in number and in size of thrips reared in both conditions suggested that the~owers were essential for the success of thrips development[ In the presence of~owers\ the distribution of females between the leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 0 publications
4
26
0
1
Order By: Relevance
“…In this study, the r value of F. occidentalis and F. intonsa was higher on cucumber leaves than that on tomato leaves, especially for F. intonsa, which is low to 0.01 on tomato leaf, this means the not suitable of tomato leaf for population development, but slowly population development would be improved in fields when added with pollens as reported in F. occidentalis (Gerin et al 1999, Hulshof et al 2003, Zhi et al 2005.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, the r value of F. occidentalis and F. intonsa was higher on cucumber leaves than that on tomato leaves, especially for F. intonsa, which is low to 0.01 on tomato leaf, this means the not suitable of tomato leaf for population development, but slowly population development would be improved in fields when added with pollens as reported in F. occidentalis (Gerin et al 1999, Hulshof et al 2003, Zhi et al 2005.…”
Section: Discussionmentioning
confidence: 46%
“…O alimento ingerido na fase larval afeta, não só o tempo de desenvolvimento, mas também o tamanho corporal do tripes. Assim, larvas maiores e mais rápidas são potencialmente menos suscetíveis a serem predadas por seus inimigos naturais (Gerin et al 1999;de Kogel et al 1999;Hulshof et al 2003).…”
Section: Resultsunclassified
“…Both larval and adult thrips of all species were predominantly found on inflorescences of their host plants rather than leaves (Figures 6.23 & 6.24). Previous studies have shown that most thrips species, including the ones investigated in the current study feed primarily on pollen and are associated with flowers (Yudin et al, 1986;Gerin et al, 1999;Milne et al, 1996). This could be the reason why large numbers of thrips were found on the flowers of weed species compared to the leaves.…”
Section: The Importance Of Flowers In Determining Abundance Of Thripsmentioning
confidence: 68%
“…This could be the reason why large numbers of thrips were found on the flowers of weed species compared to the leaves. Gerin et al (1999) showed that flowers impacted the population growth of F. occidentalis;…”
Section: The Importance Of Flowers In Determining Abundance Of Thripsmentioning
confidence: 99%
See 1 more Smart Citation